The Effect of Resilience and Entrepreneurial Mindset on the Business Sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Dayeuhkolot District - Arfani Rahmasari; Benny Bernadus (International Journal of Marketing & Human Resource Research, 2026)
MSME’s hold a strategic role in national economic stability, even though the era of disruption has significantly changed the business landscape. The complexity of the global economy poses challenges to MSME sustainability, particularly in Dayeuhkolot District, where economic uncertainty and intense competition prevail. This study analyzes the influence of resilience and entrepreneurial mindset on business sustainability, both partially and simultaneously. The approach employs a quantitative method using multiple linear regression analysis. The sample size was 100 respondents, as per the Levene test. Data were collected through a questionnaire containing a number of statements with a 1-5 Likert scale. The analytical results show that the resilience and entrepreneurial mindset variables jointly account for 39.9% of the variation in business sustainability (R Square = 0.399; p < 0.05). Partially, resilience has a significantly positive effect (β = 0.334; p < 0.05), indicating that a high level of resilience increases sustainable growth capacity. Similarly, the entrepreneurial mindset has a significant positive effect (β = 0.134; p < 0.05), supporting long-term business adaptation. However, business sustainability remains a complex phenomenon influenced by external factors beyond the scope of this research model.